Inconsistencies in assessment of pain endpoints in radiotherapy for painful tumors: Analysis of original articles in the Green and Red Journals. (September 2020) - Saito, Tetsuo; Shikama, Naoto; Yorozu, Atsunori; Kubota, Hikaru; Murotani, Kenta; Yamaguchi, Kohsei; Oya, Natsuo; Nakamura, Naoki
Highlights: The frequency of use of the ICT has risen in research for PBMs. The frequency of the ICT use has been considerably limited for PNTs. None of the journal articles had investigated non-index pain. Abstract: Background and purpose: Consistent assessment of the pain response is essential for adequately comparing treatment efficacy between studies. We studied the assessment of pain endpoints in radiotherapy for painful bone metastases (PBMs) and painful non-bone-metastasis tumors (PNTs). Material and methods: We performed a literature search in the Green (Radiotherapy and Oncology) and Red (International Journal of Radiation Oncology * Biology * Physics) Journals for full-length original articles published between 2009 and 2018. We only included articles that assessed palliation of tumor-related pain after radiotherapy. The data obtained included the definitions of pain response and assessment of non-index pain (pain other than that related to the irradiated tumors). Results: Among the 1812 articles identified using the journals' search function, 60 were included in the analysis. Thirty percent of the PBM articles and approximately half of the PNT articles did not report on analgesic use. Among the prospective studies, 68% of the articles on PBMs and 10% of the articles on PNTs used the International Consensus Endpoint. The PBM articles published in 2014–2018 utilized the International Consensus Endpoint more frequently than those published in 2009–2013 ( p  = 0.049). No articles reported information on non-index pain. Conclusions: After the initial publication of the International Consensus Endpoint, the frequency of its use appears to have risen in PBM research; however, its use in PNT studies has been considerably limited. The International Consensus Endpoint should be consistently utilized in future studies on radiotherapy for painful tumors. Since none of the journal articles had investigated non-index pain, this issue may also needs to be addressed.